Analysing regional climate forcing on historical precipitation variability in Northeast Puerto Rico. (13th December 2017) - Ramseyer, Craig A.; Mote, Thomas L.
ABSTRACT: The tropical forests of northeast Puerto Rico (NE PR) and the Luquillo Mountains (LM) are a large repository for biodiversity and have an important role in regional biogeochemical processes. Precipitation is a key driver of the productivity of these sensitive ecosystems. This study analyses historical precipitation variability from 1985 to 2014 at El Verde Field Station (EVFS) at 380 m on the north facing slope of the LM. The primary objective of this study is to identify atmospheric states that lead to extreme wet/dry conditions at EVFS. This study also investigates how those wet/dry atmospheric states change over the study period through an epoch approach on annual and seasonal timescales. Self‐organizing maps (SOMs) are used to produce atmospheric states from ERA‐Interim low‐tropospheric moisture and circulation variables. These atmospheric states are downscaled to precipitation at the EVFS rain gauge. A probability density function of observed precipitation is calculated for each atmospheric state. Changes in node frequency, which is the number of days mapping to a particular node compared to the total number of days in the temporal period, are used to evaluate changes in wet/dry atmospheric states at EVFS. Results indicate that low‐precipitation days at EVFS are associated with atmospheric states with high 1000–700 hPa bulk wind shear and decreased 700 hPa moisture. Wet days in the study region are associated with moist low‐tropospheric environments with low wind shear. Our results indicate an increased frequency of dry season atmospheric states with lower 700 hPa moisture. Over the study period, the dry season has a decrease in median and extreme precipitation during rainy days (days >0 mm). A decrease in early rainfall season median precipitation on rainy days is observed despite an increase in days with measurable precipitation, likely driven by an increase in light rainfall days (<5 mm). Abstract : Dry/wet days in the Luquillo Mountains are correlated with high/low vertical wind shear and low/high low‐ to mid‐tropospheric moisture. Dry day frequency has decreased across all seasons and has shifted to an increase in light precipitation days (<5 mm). Dry season precipitation has been experiencing a decrease in median and extreme precipitation while the early rainfall has experienced a decrease in median rainfall. Composite maps of 1000–700 hPa bulk wind shear (kts) for the 12 nodes associated with the lowest precipitation PDFs.